PENGUJIAN MEDIA TANAM KOMPOS DAN RESIDU SAMPAH RUMAH TANGGA TERHADAP BASA TUKAR, KTK, KB DAN PRODUKSI TANAMAN SAWI (Brassica juncea L. Czern) DI LAHAN PEKARANGAN KEC. SUNGGAL - Daniel H Tampubolon; Abdul Rauf; Gantar Sitanggang (Universitas Sumatera Utara, 2014)
The Study to evaluate the effect compost of household waste as growing media and the residual ofhousehold waste pit on the availability of KTK, KB and the production of mustard (Brassica junceaL. Czern) corp in yard. This research was conducted in the compost yard in Desa Sei SemayangKecamatan Sunggal Kabupaten Deli Serdang and in the laboratory of Agricultural Faculty ofUniversity of North Sumatra. The design of this research were non-factorial random design which isconsisting of 9 treatments with 3 replications. The treatment are M1 (100% soil), M2 (75% soil +25% compost), M3 (50% soil + 50% compost), M4 (25% soil + 75% compost), M5 (75% soil +25% residues of the household waste pit), M6 (50% soil + 50% residues of the household wastepit), M7 (25% soil + 75% residues of the household waste pit), M8 (50% compost+ 50% residues ofthe household waste pit), M9 (100% residues of the household waste pit). The result is that researchas household waste compost and residues of the household waste pit and the combination of both,very significantly increased the K-dd, Base Saturation of the soil as well as the production of thewet weight mustard plant and not significant to Ca, Mg and Na contensts.Keywords : Household, compost, residues , mustard (Brassica juncea L. Czern)